2010
DOI: 10.4318/tjg.2010.0075
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of laparoscopic cholecystectomy in scleroatrophic gallbladders

Abstract: Laparoscopic cholecystectomy (LC) has become the gold standard surgical procedure for symptomatic cholelithiasis. The success rate in LC is closely associated with the experience of the surgeon as well as the macroscopic appearance of the gallbladder (1). Normally, there is no distinct edema or adhe- Turk J Gastroenterol 2010; 21 (2): 156-162

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…A significant relationship was reported between number of gallbladder stones and difficulty of operation and switching to open surgery through infindibular effect of stone size. Gallbladder stone's placing on cystic duct and being large was reported to make the operation difficult and thereby lead to major complications (Akoğlu et al, 2010;Alponat et al, 1997). In our study, a significantl relationship was not found between switching to open surgery and number of gallbladder stones and increased size of stones (p>0.05).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…A significant relationship was reported between number of gallbladder stones and difficulty of operation and switching to open surgery through infindibular effect of stone size. Gallbladder stone's placing on cystic duct and being large was reported to make the operation difficult and thereby lead to major complications (Akoğlu et al, 2010;Alponat et al, 1997). In our study, a significantl relationship was not found between switching to open surgery and number of gallbladder stones and increased size of stones (p>0.05).…”
Section: Discussioncontrasting
confidence: 52%
“…It was seen that increased gall baldder wall thickness and gallbladder's being sclerotic and atrophic increased difficulty of the operation, led to complications and increased ratio of switching to open surgery (Schrenk et al, 1995;Keskin et al, 1996;Akın et al, 1998;Yol et al, 2006;Akoğlu et al, 2010;Alponat et al, 1997;Lal et al, 2002;Majeski, 2007). On the contrary to literature data, increased gallbladder wall thickness and gallbladder's being sclerotic and atrophic were not found statistically significant in terms of difficulty of operation in our study (p>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Ishikawa et al, 2 reported drain usage after laparoscopic cholecystectomy in cases defined as complicated, such as intraoperative excessive bleeding, difficult operations, and intraoperative spread of bile. 4 According to the experience and data obtained from this study, drain usage is indicated in cases such as acute complicated cholecystitis, elective scleroatrophic cholelithiasis, when smooth closure cannot be made of a cystic canal, when there is perioperative injury or bleeding, or a history of anticoagulant use. According to the findings of this study, it can be said that drain usage in cases of elective non-complicated cholelithiasis does not provide any additional benefit to the patient.…”
Section: Discussionmentioning
confidence: 96%
“…Inclusion criteria for the study were; elective uncomplicated cholelithiasis (Grade 1, 2, 3 gallbladder), American Society of Anesthesiologists (ASA) score 1-2-3 patients, and age <70 years. Uncomplicated cholelithiasis criteria were defined by the surgeon during laparoscopic cholecystectomy according to the gall bladder adhesion scoring scale defined by Akoglu et al 4 Using this scale of grade 1 = no pericholecystic adhesions, grade 2 = adhesions easily loosened with dissection, grade 3= chronic pericholecystic adhesions showing fibrotic properties permitting dissection, grade 4 = adhesions preventing the easy determination of anatomic structures and making dissection difficult, which are intense accompanied by a thickened gall bladder wall (sclero atrophic cholelithiasis). Exclusion criteria were; grade 4 gallbladder with stones, 4 conversion cholecystectomy, emergency cholecystectomy, previous upper abdominal surgery, predisposition for bleeding and chronic liver disease, gangrenous and emphysematous cholecystitis, intraoperative injury or bleeding, choledocholithiasis, cholangitis, pancreatitis, and unwillingness to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The etiology and differential diagnosis of the cholecystitis and obstructive jaundice is challenging. It would include (a) a sclerotrophic partially intrahepatic gallbladder which may give rise to the biliary pain and recurrent cholecystitis 4 ; (b) an acute acalculous cholecystitis (acute cholecystitis without cholecystolithiasis)) manifesting as a Mirizzi's syndrome, 5‐9 but for the patient having a normal white blood cell count and the presentation not meeting the full Tokyo criteria for diagnosis of acute cholecystitis 10‐12 . Acute acalculous cholecystitis (AAC) is traditionally known to occur in critically ill patients and Cyclospora cayetanensis infection of the gallbladder in the acquired immune deficiency syndrome (AIDS) patient and has a poor prognosis 13 .…”
Section: Discussionmentioning
confidence: 99%